16p-1(5p+6)=-8-2(1p+12)

Simple and best practice solution for 16p-1(5p+6)=-8-2(1p+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16p-1(5p+6)=-8-2(1p+12) equation:


Simplifying
16p + -1(5p + 6) = -8 + -2(1p + 12)

Reorder the terms:
16p + -1(6 + 5p) = -8 + -2(1p + 12)
16p + (6 * -1 + 5p * -1) = -8 + -2(1p + 12)
16p + (-6 + -5p) = -8 + -2(1p + 12)

Reorder the terms:
-6 + 16p + -5p = -8 + -2(1p + 12)

Combine like terms: 16p + -5p = 11p
-6 + 11p = -8 + -2(1p + 12)

Reorder the terms:
-6 + 11p = -8 + -2(12 + 1p)
-6 + 11p = -8 + (12 * -2 + 1p * -2)
-6 + 11p = -8 + (-24 + -2p)

Combine like terms: -8 + -24 = -32
-6 + 11p = -32 + -2p

Solving
-6 + 11p = -32 + -2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2p' to each side of the equation.
-6 + 11p + 2p = -32 + -2p + 2p

Combine like terms: 11p + 2p = 13p
-6 + 13p = -32 + -2p + 2p

Combine like terms: -2p + 2p = 0
-6 + 13p = -32 + 0
-6 + 13p = -32

Add '6' to each side of the equation.
-6 + 6 + 13p = -32 + 6

Combine like terms: -6 + 6 = 0
0 + 13p = -32 + 6
13p = -32 + 6

Combine like terms: -32 + 6 = -26
13p = -26

Divide each side by '13'.
p = -2

Simplifying
p = -2

See similar equations:

| 21x^5-27x^4+6x^3=0 | | 3(x-9)+4(x+3)= | | 0.29(x+50)-6=0.4(3x+20) | | (x+3)+(y+6)=46 | | 4.2d=-10.5 | | 7k+5=5(1-7k) | | 3(x-4)+4(x+3)= | | 48-2x=x | | .25x-0.75=-0.25x+3.25 | | x-16+2x-85+.5x+8=180 | | 7-14x=15x-16 | | 3x+y=78 | | -27t=-21.6 | | 14x^2+7x-21=0 | | -5y=8.5 | | 5t^2+15t+10=0 | | 3k-k+3=k-7 | | -4.72x=65 | | -4x^2+4x-7=0 | | 12+5z=13+5z | | 14-4t=2(17-t) | | 2(48)=x | | (x-1)(x+5)=x+4x-2 | | 2(x)=48 | | 0.089x-0.32+0.001(5-x)=0.231 | | -37=8y | | 2(h-5)h=h-10 | | 8-3x=-4x-12 | | 2(x)-8=40 | | 28-5t=2t | | 4-2=y+10 | | 3x+2=2x-11 |

Equations solver categories